2018
DOI: 10.3389/fneur.2018.00276
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Epilepsy Genetics in Africa: Is Now the Time?

Abstract: Over 80% of people with epilepsy live in low- to middle-income countries where epilepsy is often undiagnosed and untreated due to limited resources and poor infrastructure. In Africa, the burden of epilepsy is exacerbated by increased risk factors such as central nervous system infections, perinatal insults, and traumatic brain injury. Despite the high incidence of these etiologies, the cause of epilepsy in over 60% of African children is unknown, suggesting a possible genetic origin. Large-scale genetic and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 67 publications
2
30
0
Order By: Relevance
“…More research collaborations and funding are required to promote GWAS in regions with high epilepsy burden. GWAS of epilepsy in epilepsy endemic regions are expected to discover ethnically related polymorphisms and genetic diversity of epilepsy amongst different populations (167).…”
Section: Genome Wide Association Studies (Gwas) Of Sodium Channel Genmentioning
confidence: 99%
“…More research collaborations and funding are required to promote GWAS in regions with high epilepsy burden. GWAS of epilepsy in epilepsy endemic regions are expected to discover ethnically related polymorphisms and genetic diversity of epilepsy amongst different populations (167).…”
Section: Genome Wide Association Studies (Gwas) Of Sodium Channel Genmentioning
confidence: 99%
“…The MOCR inhibits outer hair cell (OHC) activity in the cochlea, reducing the OHC gain (Gifford & Guinan, 1987; Liberman & Brown, 1986; Siegel & Kim, 1982; Warr & Guinan, 1979). Among other putative MOCR functions, this gain reduction is thought to aid signal detection in noise (for reviews, see Guinan, 2006; Lopez-Poveda, 2018). The role of the MOCR in signal detection in noise is particularly relevant for children who complain of listening difficulties (LiD).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there was no association between these SNP genetic haplotypes and drug resistance, contrasted with previous studies that showed an association of these genotypes with response to AEDs. 18,19 CYP3A5 rs15524 was found to be related to the metabolism of the AEDs such as tacrolimus and carbamazepine; 20,36,37 however, there is a lack of data regarding its association with epilepsy. Emich-Widera et al failed to confirm the association of CYP3A5 polymorphism with drug resistance in Caucasian children with epilepsy.…”
Section: Discussionmentioning
confidence: 99%